AB0347 Effects of Physical Activity and Anti-TNF-Alpha Disease Control on Lipid Profile of Rheumatoid Arthritis Patients. (9th June 2015) - Cacciapaglia, F.; Iervolino, S.; Anelli, M.G.; Mazzotta, D.; Zincarelli, C.; Pappone, N.; Iannone, F.; Lapadula, G.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic inflammatory disease associated with reduced life expectancy mainly due to an increased incidence of cardiovascular diseases (CVD). Chronic inflammation seems to play a key role in accelerated rate of CVD in RA. Exercise is commonly used to reduce metabolic CV risk factors, but as disease activity influences both inflammatory status and movement capability of RA patients, several studies lack to understand the real outcome of biological treatment on lipid profile, and conflicting results have been found for anti-TNF agents. Objectives: To investigate the effect of a structured rehabilitation program on lipid profile of RA patients with low-disease activity/remission during anti-TNF treatment. Methods: This study included RA patients, referred to our outpatient clinics from June to December 2013, achieving the DAS28<2.6 after 12 weeks of anti-TNF and DMARDs, and belonging to the II class of the ACR global functional classification. Patients were randomized into 2 groups: Group 1) underwent a 6-week-lasting twice/daily comprehensive rehabilitation, defined as systematic multidisciplinary treatment; Group 2) had their habitual daily physical activity without any adjunctive rehabilitative intervention. Disease activity and lipid profile (Total Cholesterol, HDL-C, LDL-C, Triglycerides, Atherogenic Index) were measured before and after 12 weeks. Results: We enrolled 40 patients (29 female; mean age 57±13 years; mean disease duration 7±5 years) with DAS28-CRP<2.6 in the ACR functional class II, and 19 patients underwent to the rehabilitative program (Group 1). After the observational period no disease flare were observed. We recorded a significant reduction of the atherogenic index and a HDL-C increasing in both study groups, but only in the Group 1 we detected a significant reduction of the Total Cholesterol and LDL-C (see Table ). Conclusions: The suitable control of inflammation seems to have a main influence only on HDL-C while structured physical activity not only improves functional performance in RA patients but also results in a more favorable modification in lipid profile, with Total-C and LDL-C reduction too. The effective control of inflammation and disease activity and a full management of the several CV risk factors, also with physical activity, are a key challenge to improve RA patients health. Disclosure of Interest: None declared